Robust GNN-Based Representation Learning for HLS - Sohrabizadeh, Atefeh; Bai, Yunsheng; Sun, Yizhou; Cong, Jason (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2023)
The efficient and timely optimization of microarchitecture for a target application is hindered by the long evaluation runtime of a design candidate, creating a serious burden. To tackle this problem, researchers have started using learning algorithms such as graph neural networks (GNNs) to accelerate the process by developing a surrogate of the target tool. However, challenges arise when developing such models for HLS tools due to the program's long dependency range and deeply coupled input program and transformations (i.e., pragmas). To address them, in this paper, we present HARP ( H ierarchical A ugmentation for R epresentation with P ragma optimization) with a novel hierarchical graph representation of the HLS design by introducing auxiliary nodes to include high-level hierarchical information about the design. Additionally, HARP decouples the representation of the program and its transformations and includes a neural pragma transformer (NPT) approach to facilitate a more systematic treatment of this process. Our proposed graph representation and model architecture of HARP not only enhance the performance of the model and design space exploration based on it but also improve the model's transfer learning capability, enabling easier adaptation to new environments 1 1 All materials available at https://github.com/UCLA-VAST/HARP.